Pressure fluctuations in shear flow turbulence Part 1 and part 2 - Hodgson, T. H. (College of Aeronautics, 1962)
An investigation of the fluctuating pressure in turbulent shear flaws at low Mach numbers is described. The treatment is both theoretical and experimental although, in the latter case, present limitations of pressure transducer design have restricted the experiments to surface measurements in wall shear flows over rigid plane boundaries. The turbulent flat-plate boundary layer is studied in detail. Calculations from existing turbulent, velocity data show that the ratio of the root-mean-square wall, fluctuating pressure to free stream dynamic pressure is approximately twice the local skin friction coefficient Cf. . The dependence on Cf has been verified for the Reynolds number range 3 x 105 to 8 x 106. The factor of proportionality was 2.2. Although part of the test programme was performed in a low-noise wind-tunnel, it was not possible to determine completely the pressure power spectral density from laboratory measurements. This problem has been resolved by full-scale flight measurements on the wing of a high performance glider. The power spectral density of the surface pressure fluctuations was found to vary as the square of the frequency at low frequencies, a result in agreement with analysis of the turbulence-mean shear contribution, to the wall pressure … [cont.].